If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + -9) + 14x = 0 Reorder the terms: 3(-9 + 3x) + 14x = 0 (-9 * 3 + 3x * 3) + 14x = 0 (-27 + 9x) + 14x = 0 Combine like terms: 9x + 14x = 23x -27 + 23x = 0 Solving -27 + 23x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 23x = 0 + 27 Combine like terms: -27 + 27 = 0 0 + 23x = 0 + 27 23x = 0 + 27 Combine like terms: 0 + 27 = 27 23x = 27 Divide each side by '23'. x = 1.173913043 Simplifying x = 1.173913043
| 535+.21x=850 | | 230-x=15 | | 7(x+5)=6x+45 | | 228+-x=75 | | 55+x+4x-5=180 | | 4.9t^2+10t-61=0 | | 3y-21=-28+2y | | 3u-5=8u-20 | | 5v+2=32 | | 24b-12=5b | | 350000=350000-.11x | | 3y+9=10y+30 | | x=(90-x)-12 | | X+.11=350000 | | 17-9x=71 | | 5/12=b/5 | | 8+3w=23 | | 3x+66=360 | | 3u-5=8u-28+8 | | A^2(5a+2)(a+2)=0 | | X^2+4x-6=12 | | 8=3m-16 | | k^3-k^2-4k+4=0 | | x^2+5x-6=12 | | X-3=180 | | -13=y-4 | | x^4+5x-6=12 | | (3.250+2.75)*2= | | (+6+-2)*-3= | | a-(2-5a)=4 | | 5.5r+7.2m=-12 | | .10*27000= |